Police state: how America's cops get away with murder - Spence, Gerry (St. Martin's Press, 2015)
"We all want to feel safe. But safe from what, and from whom? In his 60-plus years as a trial lawyer, Gerry Spence has never represented a person accused of a crime in which the police hadn't themselves violated the law. Whether by covering up their own corrupt dealings, by the falsification or manufacture of evidence, or by the outright murder of innocent civilians, those individuals charged with upholding the law break it every day, in ways more scandalous than the courts have dared admit. The police and prosecutors won't charge or convict themselves, and so the crimes of the criminal justice system are swept under the rug. Nothing changes. Too many police officers are killers on the loose, and every uninformed American is a potential next victim. Police culture is mired in the dead weight of precedent and ruled by trigger-happy tyrants. Power will march our nation over the police state precipice unless We the People take action. The FBI's massacre of the Weaver family at Ruby Ridge; the killing of mortally-wounded Fouad Kaady by a group of police officers; the torture of teenaged Dennis Williams by cops seeking a murder confession-again and again, the question arises: When the very men and women we pay to protect us instead persecute us every day, how can we be safe? In Police State, Spence slaps a stinging indictment upon the American justice system and puts forth a plan to restore liberty and justice for all"--